Loss and recuperation in the Singaporean experience - Diaz, Ma. Rommin M. (College of Arts and Letters, University of the Philippines Diliman, 2011)
This thesis seeks to contribute to the study of the loss and recuperation in Singaporean literature by analyzing the novels of Philip Jeyaretnam, namely: Abraham's Promise (1995), Raffle Place Ragtime (1988) , and First Loves (1987). Questions on what is lost and how one recovers from such infirmity, if the individual ever does at all, are its foremost concerns. To better grasp the nature of loss and to be able to recognize its various shapes and manifestations, this study sought to answer the following questions: What are the losses that plague that Singaporean individual? What are the origins of these losses and how can these origins be explained? Does the individual recover from the loss he is afflicted with? If he does, then, what recuperative mechanisms does he employ and what do these entail? The study consider loss as "an active, creative, productive force, rather than an inevitable, solipsistic, helpless attachment to an irrevocable absence" (175). It renders the loss as an "affirmative, productive concept... as a site of myriad possibilities" (Mandel 117). This suggests that individuals infirmed by loss, no matter how profound, are afforded a chance of recovery. This thesis seeks fill a gap in studies on Singaporean literature. While there is a proliferation of studies on Singaporean literature, scholarly works that focus on the loss and recuperation appear scant. Addressing this gap will enhance our understanding of the Singaporean sensibility and contribute to Asian literary scholarship. This study also reveals circumstances, challenging or otherwise, that Filipinos who are living and working in Singapore may find themselves in. As the title of Dodo Certeza's article "The Changing Face of Filipinos in Singapore in the Philippine Star dated 19 November 2008 implies, not all Filipinos who strive in the city-state are domestic helpers. There is now a diversity in profession, as even the educated Filipinos find the prospect of working in Singaporean more lucrative than in the Philippines. Filipinos in Singapore may suffer the same losses that the Singaporeans experience but, definitely, to a greater degree. since they are in a foreign soil and thus, are distanced from their love ones, from comfortable, and the comfortable, familiar surroundings of home. Filipinos abroad are subject to alienation an culture shock, thereby, exacerbating the feeling of loss and rendering the difficult the act of coping. Thus, the relevance of my work.